Introducing Electronic Systems Concepts Using Old Computers - Watson, Dennis G.; Pense, Seburn L.; Harrison, Tony V.; Steffen, Richard W. (Journal of Agricultural Systems, Technology, and Management, 2005)
An existing agricultural electricity course was revised to include electronic systems. An electronic systems unit was developed using computer components as an example of an electronic system. The unit introduced students to the terminology, technology and components of computer systems. Students removed and reassembled all components of a computer to obtain hands-on experience. The hands-on exercise emphasized work skills of attention to detail, precision and quality. The electronic systems unit was evaluated over two terms with quantitative and qualitative means. Student knowledge increased an average of thirty-three percent, based on pretest and posttest results. Eighty-four percent of the students said the content was beneficial to them.